Just entertainment? Student and faculty responses to the pedagogy of media representations of higher education. (2nd January 2020) - Marquis, Elizabeth; Johnstone, Katelyn; Puri, Varun
ABSTRACT: Hollywood film has been positioned as a form of public pedagogy – a site of efficacious informal learning. Acknowledging this educative potential, this article examines the ways in which faculty and students perceive and respond to representations of higher education offered by popular film. Drawing on focus groups and interviews with 22 participants, we discuss the key themes about teaching and learning that faculty and students observed in filmic representations – including an emphasis on genius, the presence or absence of effort, and a prevalence of extreme faculty-student relationships – and consider the extent to which these lessons shape viewers' understanding and experiences of teaching, learning, and universities. While many participants suggested these representations are 'just entertainment' and thus have limited impact, their comments nonetheless indicate ways in which films shape their own and others' experiences and perceptions of the university, underscoring the need for further research in this area.